Pemenuhan Kesejahteraan Psikologis Wanita dengan Peran Ganda Berdasarkan Amsal 31:10-31 - Merisa Dilang; Yanto Paulus Hermanto (Institut Agama Kristen Negeri Kupang, 2022)
Women with dual roles as full-time housewives and career women have time management and work pressures that leave less time for themselves which affects women's physical, emotional and social well-being. Women with multiple roles tend to be easily stressed and depressed. The purpose of this study is to provide an overview of the fulfillment of women's psychological well-being with multiple roles from the perspective of Proverbs 30:11-31. The research method uses a qualitative approach with a descriptive method. The qualitative method is carried out by studying literature on references and scientific literature related to the fulfillment of the psychological well-being of women with dual roles based on Proverbs 31:10-31 studied from the aspect of psychological well-being. The fulfillment of psychological well-being consists of aspects of self-acceptance, positive relationships with others, independence, environmental mastery, life goals and personal growth. This aspect is described in the criteria of a capable wife who is a double role woman in Proverbs 31:10-31. These criteria include being trustworthy, generous, diligent workers, good housekeepers, thinking about the future, and having inner beauty.